Linking Ocean's Benefits to People (OBP) with Integrated Ecosystem Assessments (IEAs). Issue 1 (24th September 2020) - Belgrano, Andrea; Villasante, Sebastián
Abstract: The fundamental challenge of the inclusion of the human dimension of the oceans in the Integrated Ecosystem Assessments (IEAs) provides an opportunity for a transdisciplinary approach to create synergies between the current research by the International Council for the Exploration of the Sea (ICES) and the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services (IPBES). We have highlighted the importance of ocean inequality as a critical aspect to consider to unlock current barriers to integrate social sciences in marine integrated assessments. To create bridges between them, we develop an Ocean's Benefits to People (OBP) framework that embraces the blue economy, equity, the UN SDGs goals and support an Ecosystem‐Based Management (EBM) for the oceans. Abstract : The fundamental challenge of the inclusion of the human dimension of the oceans in the Integrated Ecosystem Assessments (IEAs) develop an Ocean's Benefits to People (OBP) framework that embrace the blue economy, equity